DOP35 Innate immune dysregulation, detectable up to 6 years before the diagnosis of Crohn's disease, is significantly amplified in patients with a complicated phenotype. (25th January 2019) - Choung, R S; Petralia, F; Torres, J; Sato, T; Li, X-j; Wang, P; Telesco, S; Porter, C; Laird, R; Gutierrez, R; Princen, F; Plevy, S; et al.
Abstract: Background: Crohn's disease (CD) is a progressive and destructive disease. At diagnosis, up to 1/3 of patients have a complicated phenotype defined as stricturing (B2), internal penetrating (B3) CD, or surgery. We evaluated anti-microbial antibodies and protein markers in multiple samples long before diagnosis to assess whether complicated vs. non-complicated CD at diagnosis was associated with pre-diagnostic biomarkers. Methods: Pre-diagnosis serum samples ( 2, 4, and 6 years prior to diagnosis) were obtained from 200 patients with CD and 200 healthy controls (HC). Samples were tested for a panel of anti-microbial antibodies and 1129 protein markers (SomaLogic panel). A complicated CD phenotype at diagnosis was defined based on ICD-9 or CPT codes (B2, B3, or surgery). The association between each marker and complication was assessed via Cox regression. Significant markers passing a false-discovery rate of 20% were selected for different time before diagnosis (−2Y, −4Y, and -6Y). In addition, for proteomic markers, biological pathways enriched in the set of predictive markers were identified via Fisher exact test. Results: Forty-seven subjects (24%) had a B2 ( n = 36) or B3 ( n = 9) phenotype or surgery ( n = 2) at diagnosis. Figure 1 shows anti-microbial antibodies as well as protein markers selected at different years before diagnosis. At 6 years prior to diagnosis, the difference of anti-microbial antibody titers was already significant between complicated and non-complicated CD. Thirty protein markers, involved in the activation of immune system and/or inflammation, were associated with complicated CD. Most protein markers such as CRP, C9, and C5 were up-regulated, while few markers including SERPINA4 and c-Kit were down-regulated in patients developing complications. Pathway analysis identified higher activation of the innate immune system and complement/coagulation cascades for both 4 and 6 years before diagnosis in complicated CD vs. uncomplicated CD. The difference of those activated pathways was prominent at 6 and 4 years before diagnosis and disappeared as approaching the time of diagnosis. Most of pre-diagnostic biomarkers were increased in both complicated and non-complicated CD vs. healthy controls. Conclusions: Complicated CD at diagnosis is associated with higher serum levels of anti-microbial antibodies and a different profile of proteins, vs. non-complicated CD, years before diagnosis. Findings suggest that innate immune activation with involvement of complement pathways occur early in the natural history of complicated CD many years before diagnosis.